Peningkatan Kualitas Produk Knalpot Aftermarket Purbalingga melalui Penerapan Teknologi Paten, Lean Manufacturing, Manajemen K3, serta Peningkatan Teknologi Manufaktur - Ahmad Roziqin; Arif Ainur Rafiq; Ahmad Mustamil Khoiron; Bayu Wiratama (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service program aims to improve the quality of exhaust products through the application of patent-based technology IDS000008763 to reduce noise and patent IDS0020231494 to reduce exhaust emissions for two service partners, RCM Java Racing and JRC Muffler. The service implementation method included lectures and discussions during regulatory outreach activities, demonstrations and practical exercises during technology training activities, implementation of an OHS management system and lean production, and improvements in manufacturing technology. The results of the service program showed an increase in the production capacity of JRC and RCM partners from 100 to 150 units per month, a 50% reduction in waste through the implementation of lean manufacturing, and an improvement in the quality of emissions and product noise in accordance with government regulations. Management transformation was achieved with an 89% reduction in the OHS incident rate. This program successfully transformed the exhaust MSME from an informal sector to a business oriented towards quality, regulation, and sustainability.